Application of the self-similarity of chaotic processes for digital communication systems - Politansky, Ruslan; Politansky, Leonid; Ivanyuk, Petro (Видавництво Львівської політехніки, 2012)
In this paper investigate the possibility of using fractal features of the superposition of noise signals in order to design a digital communication system.
Keywords: chaotic processes; self-similarity; Hurst parameter